2014
DOI: 10.5505/kjms.2014.64936
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modification of lifestyle on reproductive potential

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 37 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Lifestyle factors could affect reproductive health either positively or negatively (Ilacqua et al, 2018). Infertility can be defined as the absence of conception within one year of unprotected sexual intercourse, while fertility is the capability of producing an offspring (Aydin et al 2014). The new trend of modern lifestyle is that people delay starting a family due to educational and career pursuit, such individuals are older and overweight.…”
Section: Major Lifestyle Behaviors That May Affect Fertilitymentioning
confidence: 99%
See 4 more Smart Citations
“…Lifestyle factors could affect reproductive health either positively or negatively (Ilacqua et al, 2018). Infertility can be defined as the absence of conception within one year of unprotected sexual intercourse, while fertility is the capability of producing an offspring (Aydin et al 2014). The new trend of modern lifestyle is that people delay starting a family due to educational and career pursuit, such individuals are older and overweight.…”
Section: Major Lifestyle Behaviors That May Affect Fertilitymentioning
confidence: 99%
“…The quality of sperm parameters of men performing the exercise for one hour, at least three times a week were 15.2% better than that those who perform exercise less frequently or excessively (9.7%). The parameters investigated by the authors were the morphology, count, concentration, and motility (Aydin et al, 2014) Studies have associated STIs with risk for male infertility in southern Nigeria (Okonofua et al, 2005), and men who reported having chronic penile discharge, painful micturition, genital ulcers, and testicular pain were more likely to be infertile. Another study reported 173/500 (34.6%) of STIs prevalence among males investigated for infertility in Kano, Northern Nigeria (Emokpae et al, 2009).…”
Section: Physical Exercisementioning
confidence: 99%
See 3 more Smart Citations